2017
DOI: 10.1002/aet2.10049
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Emergency Medicine Physicians’ Use of Point‐of‐care Ultrasound and Barriers to Implementation: A Regional Pilot Study

Abstract: Objectives: Point-of-care ultrasound (POCUS) has been identified as a critical skill for pediatric emergency medicine (PEM) physicians. The purpose of this study was to profile the current status of PEM POCUS in pediatric emergency departments (EDs).Methods: An electronic survey was distributed to PEM fellows and attending physicians at four major pediatric academic health centers. The 24-item questionnaire covered professional demographics, POCUS experience and proficiency, and barriers to the use of POCUS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 29 publications
3
39
0
Order By: Relevance
“…As such, learning POCUS has become an increasing priority in PEM, with the learning experience typically including introductory courses and skill acquisition that relies on case‐by‐case clinical exposure . However, this approach may lead to challenges in achieving POCUS proficiency across a wide range of learners . Opportunities for bedside feedback may be limited by the number of POCUS‐trained attendings available at a given site .…”
mentioning
confidence: 99%
“…As such, learning POCUS has become an increasing priority in PEM, with the learning experience typically including introductory courses and skill acquisition that relies on case‐by‐case clinical exposure . However, this approach may lead to challenges in achieving POCUS proficiency across a wide range of learners . Opportunities for bedside feedback may be limited by the number of POCUS‐trained attendings available at a given site .…”
mentioning
confidence: 99%
“…24 Another study 25 showed that the most significant barriers to POCUS documentation were time constraints, the existence of a separate computer program for POCUS documentation, and problems with the USG machines. One significant barrier according to a pilot study 26 relates to the need for dedicated time to learn and practice POCUS to achieve sufficient levels of proficiency for use in practice. In our context, with the help of the collaborators, addressing the barrier, DH is able to equip all the outreach centers with basic USG facility.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound must also be practiced regularly in order to maintain competency. This may be an unrealistic undertaking for a previously unskilled, or busy clinician, regardless of their motivation to provide the service …”
Section: Limitationsmentioning
confidence: 99%